Analysis of Financial Performance on Stock Price with Price Earning Ratio as a Moderation Variable (Case Study of Tourism and Hospitality Industries) - Artanto, Alethia Veritas Nico (SEIKO : Journal of Management & Business, 2023)
This research wants to re-examine Return On Equity, Earning Per Share and Current Ratio, which affect stock prices with the Price Earning Ratio as a Moderating Variable by observing tourism companies, hotels and restaurants listed on the Indonesia Stock Exchange in the 2018 – 2020 period. This research method uses a type of inferential quantitative research. The results of this study show that Return On Equity (ROE) does not contribute to changes in share prices of tourism companies, hotels and restaurants listed on the Indonesia Stock Exchange for 2018 – 2020. The current Ratio (CR) does not contribute to changes in share prices of tourism companies, hotels and restaurants listed on the Indonesia Stock Exchange for the 2018 – 2020 period. Earning Per Share (EPS) contributes to changes in the share prices of tourism companies, hotels and restaurants listed on the Indonesia Stock Exchange for 2018 – 2020. The Price Earning Ratio (PER) is not a moderate Return On Equity (ROE) to changes in share prices of tourism companies, hotels and restaurants listed on the Indonesia Stock Exchange for 2018 – 2020. Price Earning Ratio (PER) cannot moderate Current Ratio (CR) to changes in share prices of tourism companies, hotels and restaurants listed on the Indonesia Stock Exchange for 2018 – 2020. The Price Earning Ratio (PER) cannot moderate Earning Per Share (EPS) on changes in share prices of tourism companies, hotels and restaurants listed on the Indonesia Stock Exchange for 2018 – 2020.